We Deserve Monuments - Hammonds, Jas (New York : Roaring Brook Press, 2022)
When seventeen-year-old Avery moves to rural Georgia to live with her ailing grandmother, she encounters decade-old family secrets and a mystery surrounding the town's racist past.
New YA Book 2023 Winter.
Ages 14-18.
Grades 10-12.
Keywords: Family problems -- Fiction; Secrets -- Fiction; African Americans -- Fiction; Racism -- Fiction; Lesbians -- Fiction; Fiction